PERBEDAAN HARMONI SOSIAL PENGHUNI RUMAH SUSUN DAN PENGHUNI RUMAH TAPAK DI KAWASAN TEBET, JAKARTA - Hanny Wahidin Wiranegara; Putri Arninda; Yosua Harefa (TATALOKA, 2018)
Housing development has to be directed to establish a spatial community characterized by the bond among members and place attachment to their living space. The moving outside of inhabitants can be caused by low social harmony or low functional conditions of their housing. It can be happened in flats as well as in landed housing. Social harmony is the condition of the bond among inhabitants including a bond of value, a bond of feeling, and a common action. It is an important element to establish a community. This research aims are identifying the difference of social harmony between the inhabitants of flats and landed houses, as well as identifying the elements of functional conditions of housing that affect social harmony. The research design used questionnaire survey using Likert’s scale. Tebet area was chosen as the study area because there are landed houses and flats inside. The results showed that there was the difference of social harmony between the two types of housing. Social harmony in flats was lower. There are two kinds of housing functions affecting social harmony in both types of housing were economic function and service function. Hence, in housing planning besides the availability of social-economic facilities and utilities, also important to be considered about how these function running well in order to keep the social harmony among its inhabitants next come into being as a community.